2006
DOI: 10.1097/00001756-200604240-00016
|View full text |Cite
|
Sign up to set email alerts
|

Pedunculopontine nucleus electric stimulation alleviates akinesia independently of dopaminergic mechanisms

Abstract: The symptom of Parkinson's disease that is most disabling and difficult to treat is akinesia. We have previously shown that low-frequency stimulation of the pedunculopontine nucleus can alleviate such akinesia in a macaque rendered Parkinsonian using 1-methyl 4-phenyl 1,2,3,6-tetrahydropyridine. Here, we have extended that study to show that adding stimulation of the pedunculopontine nucleus to levodopa treatment in this Parkinsonian monkey increased its motor activity significantly more than levodopa alone. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 9 publications
3
35
0
Order By: Relevance
“…However, GABA antagonism significantly increases the overall motor activity and improves balance and posture in MPTP-treated monkeys [32] . In addition, lowfrequency PPN DBS (5-10 Hz) improves the activity of MPTP-treated monkeys, especially when added to levodopa treatment [32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…However, GABA antagonism significantly increases the overall motor activity and improves balance and posture in MPTP-treated monkeys [32] . In addition, lowfrequency PPN DBS (5-10 Hz) improves the activity of MPTP-treated monkeys, especially when added to levodopa treatment [32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, chemical and electrical stimulation has been shown to drive locomotor activity in rat [33], feline [34][35][36], and primate studies [37][38][39]. Recently, it has been demonstrated that the effects are additive to levodopa therapy after use of the dopaminergic neuronspecific toxin MPTP in primates [40]. This supports a role for cholinergic neuronal subpopulations as participants in PPN-regulated locomotor activity.…”
Section: Preliminary Clinical Experiences the Pedunculopontine Nucleusmentioning
confidence: 99%
“…The descending connections of the PPN are especially important to document as the PPN is thought to have a role in locomotion independent of the dopaminergic pathways of the basal ganglia. 12,47 Future study could involve running PDT from single seed voxels located in the deep cerebellar nuclei and seeing whether connections with the PPN seed mask become evident. Probing the connections of other single seed voxels within the PPN may yield evidence of connections between the PPN, cerebellum, and spinal cord.…”
Section: Rhesus Monkey Ppn Anatomy Determined Using Pdt Compared To Mmentioning
confidence: 99%
“…Although the evolution of such dramatic topographical differences between the human and monkey PPN initially seems unlikely, the role of the PPN has evolved dramatically from the governance of behaviours primarily related to reward and motivation in rodents 48 to what is apparently a more direct role in the induction of locomotion in higher primates. 1,3,8,9,47,49,50 Perhaps the differences between the organisation of human and monkey PPN connections can also be attributed to a changing role for the PPN in maintaining bipedal as opposed to quadrupedal gait. However, since very few studies have described the organisaton of PPN connections, our results need to be verified using additional brains before drawing any further conclusions.…”
Section: Monkey Ppn Anatomy Compared To Human Ppn Anatomy Using Pdtmentioning
confidence: 99%